Concentrated insulins: the new basal insulins - Lamos EM; Younk LM; Davis SN (Dove Medical Press, 2016)
Elizabeth M Lamos,1 Lisa M Younk,2 Stephen N Davis3 1Division of Endocrinology, Diabetes and Nutrition, 2Department of Medicine, University of Maryland School of Medicine, 3Department of Medicine, University of Maryland Medical Center, Baltimore, MD, USA Introduction: Insulin therapy plays a critical role in the treatment of type 1 and type 2 diabetes mellitus. However, there is still a need to find basal insulins with 24-hour coverage and reduced risk of hypoglycemia. Additionally, with increasing obesity and insulin resistance, the ability to provide clinically necessary high doses of insulin at low volume is also needed. Areas covered: This review highlights the published reports of the pharmacokinetic (PK) and glucodynamic properties of concentrated insulins: Humulin-R U500, insulin degludec U200, and insulin glargine U300, describes the clinical efficacy, risk of hypoglycemic, and metabolic changes observed, and finally, discusses observations about the complexity of introducing a new generation of concentrated insulins to the therapeutic market. Conclusion: Humulin-R U500 has a similar onset but longer duration of action compared with U100 regular insulin. Insulin glargine U300 has differential PK/pharmacodynamic effects when compared with insulin glargine U100. In noninferiority studies, glycemic control with degludec U200 and glargine U300 is similar to insulin glargine U100 and nocturnal hypoglycemia is reduced. Concentrated formulations appear to behave as separate molecular entities when compared with earlier U100 insulin analog compounds. In the review of available published data, newer concentrated basal insulins may offer an advantage in terms of reduced intraindividual variability as well as reducing the injection burden in individuals requiring high-dose and large volume insulin therapy. Understanding the PK and pharmacodynamic properties of this new generation of insulins is critical to safe dosing, dispensing, and administration. Keywords: degludec, concentrated insulin, glargine, Humulin-R U500, hypoglycemia, type 2 diabetes, type 1 diabetes